Oneness of God’s Concept from Rimba Watualang - Hanifah Hikmawati; Titis Srimuda Pitana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2018)
This article examines the intelligence process and attitude of Islamic Teens of Watualang (Remaja Islam Watualang or it is abbreviated as Riswa) which is quite striking in terms of the religious progressivity agenda. The agenda is arranged to have a synergy with the concept of nationalism and nationality. The group comes to the society as the efforts to reaffirm the understanding of Islamic as Ahlussunah Waljamaah in the middle of the religious extremism and radicalism. The encouragement for oneness of God (Tauhid) concept from Riswa becomes the pattern of syncretic Islam. It is implemented by Riswa to convince the teens to promote the moderate concept of Islam. The conception developed over the vision is to foster the pillars of humanity which includes ukhuwah insaniyyah, ukhuwah Islamiyyah, and ukhuwah wathaniyyah. In order to find out the fundamental motivation of Riswa’s establishment, the authors managed two research problems to clearly examine the research findings. They are: (1) What is the reason of the Islamic Teens of Watualang’s establishment? (2) How do the group members implement intelligence attitude to identify the moderate and syncretic pattern of Islamic preaching? The theory of intelligence and adaptation are implemented as a motivational breakdown analysis to obtain Riswa’s legitimacy. The above explanation is elaborated in a descriptive analysis and model forms.